Implementasi Metode Rapid Application Development pada Sistem Informasi Harga Barang Berbasis Web di Perusahaan Cipta Warna Digital Printing Boyolali - Yudha Pratama; Fera Tri Wulandari; Wisnu Sanjaya (Universitas Boyolali, 2023)
Cipta Warna Digital Printing is a printing company located in Boyolali city, this company provides various printing needs. Based on the results of interviews with the owner of the company, Cipta Warna Digital Printing has a problem, namely that it does not yet have a website, so it is difficult for the company to provide information about products, especially the available products and product prices. Based on these problems, the authors build a web-based system that is able to provide information about companies, products and allows customers to calculate product prices independently. This system is designed with Unified Modeling Language (UML) using CMS Wordpress and Rapid Application Development (RAD) method. The results of testing using Blackbox Testing show that the system runs according to its function without any errors.